2013
DOI: 10.1530/rep-12-0216
|View full text |Cite
|
Sign up to set email alerts
|

The caspase-dependent apoptosis gradient in the testis of the blue shark, Prionace glauca

Abstract: The severe degenerative phenomena that characterises spermatogenesis in mating blue sharks involves spatially separated germ cell and Sertoli cell apoptosis. Unlike that observed in multilayered type B spermatogonial and spermatocyte cysts caspase-3-dependent apoptosis of single and multinucleate type B spermatogonia in one to three spermatogonial layered cysts resulted in their complete fragmentation, delayed phagocytic removal and displacement of the apoptotic bodies towards the perilumenar Sertoli nuclei. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…Although several caspases have been found to be involved in the apoptosis of germ cells,1617 the relationship between caspase 7 and germ cells apoptosis has never been reported. Then, we constructed the models of spermatogenic dysfunction by busulfan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several caspases have been found to be involved in the apoptosis of germ cells,1617 the relationship between caspase 7 and germ cells apoptosis has never been reported. Then, we constructed the models of spermatogenic dysfunction by busulfan.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report that caspase signal pathways are relative to the apoptosis of germ cells 1617. However, whether the function of caspase 7 is involved in spermatogenesis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier analysis of the life–death balance in germ cell cohorts during spermatogenesis found that the large mature, rather than the small immature spermatogonial cysts of summer breeding P. glauca displayed a protracted two‐stage form of caspase 3‐dependent cell death, all of which allowed the distinction between two types of testicular conditions in these wild‐caught specimens (McClusky, ). The latter study distinguished histologically between testes that showed extensive multinucleate cell death (MNC) in preferentially mature spermatogonial cysts, and those with vacuolated areas in the spermatogonial layers of the same cyst stages.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative analyses of the apoptosis gradient in the expansive premeiotic (PrM) regions of Squalus (McClusky, ) and P. glauca (McClusky, , ) noted the low incidence of multinucleate cell (MNC) corpses among immature PrM cysts and their preponderance among mature PrM cysts. In both elasmobranchs, some developing PrM cysts that display a scattering of MNC death corpses may yet recover from the earlier graded onset of cell death since such cysts simultaneously display mitotic and apoptotic activity in different parts of the cysts as well as between neighboring spermatogonia (McClusky, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation